Reported burnout among U.S. general surgery residents: A survey of the association of program directors in surgery members (2020)
Introduction The literature remains unclear on the development, consequences, and interventions for burnout in resident populations. We aim to identify the prevalence and nuances of reported burnout in general surgery resident physicians to better understand which factors contribute the greatest risk. Methods A 42-question anonymous online survey was distributed by the Association of Program Directors in Surgery (APDS) to general surgery resident physicians. ANOVA, chi-square and multinomial regression analyses were performed with significance defined as p < 0.05. This survey was reported in line with the STOCSS criteria. Results 81 survey responses were received. Burnout was reported by 89.5% of university-hospital affiliated respondents and 95.2% of community teaching hospital affiliated respondents. After adjustment, community respondents showed a nearly fifteen times greater likelihood of burnout (aOR = 14.735, 95% CI: 0.791,274.482). Females were 2.7 times as likely as males to report burnout (aOR = 2.749, 95% CI: 0.189,39.960) and nearly twice as likely to report contemplating suicide (aOR = 1.819, 95% CI: 0.380,8.715). Burnout rates by hours worked/week revealed that 100% of those working ≥80 h/week report experiencing burnout. Conclusion Overall burnout rates reported by surgical residents respondents were high. Community teaching hospital setting, female gender, and increased number of hours worked per week may be associated with higher rates of burnout. Both female and community-affiliated residents were at increased risk of reporting suicidal ideation. Targeted interventions are needed to adequately address program-specific causes for resident burnout and reduce its prevalence in high-risk cohorts.